Eight amino acids form the ATP recognition site of Na(+)/K(+)-ATPase - Kubala, Martin; Teisinger, Jan; Ettrich, Rüdiger; Hofbauerová, Katerina; Kopecký, Vladimír; Baumruk, Vladimír; Krumscheid, Rita; Plásek, Jaromír; Schoner, Wilhelm; Amler, Evzen (Biochemistry, 2003)
Point mutations of a part of the H(4)-H(5) loop (Leu(354)-Ile(604)) of Na(+)/K(+)-ATPase have been used to study the ATP and TNP-ATP binding affinities. Besides the previously reported amino acid residues Lys(480), Lys(501), Gly(502), and Cys(549), we have found four more amino acid residues, viz., Glu(446), Phe(475), Gln(482), and Phe(548), completing the ATP-binding pocket of Na(+)/K(+)-ATPase. Moreover, mutation of Arg(423) has also resulted in a large decrease in the extent of ATP binding. This residue, localized outside the binding pocket, seems to play a key role in supporting the proper structure and shape of the binding site, probably due to formation of a hydrogen bond with Glu(472). On the other hand, only some minor effects were caused by mutations of Ile(417), Asn(422), Ser(445), and Glu(505).
Keywords: Models, Molecular; Genetic Vectors; Glutamine; Point Mutation; mozek; spektroskopie infračervená s Fourierovou transformací; Amino Acids; Protein Binding; vodíková vazba; sekundární struktura proteinů; Brain; rekombinantní fúzní proteiny; Mice; testy genetické komplementace; zvířata; Spectrophotometry, Infrared; glutamin; Binding Sites; vazebná místa; Adenosine Triphosphate; Spectroscopy, Fourier Transform Infrared; sodíko-draslíková ATPasa; fenylalanin; Hydrogen Bonding; molekulární modely; adenosintrifosfát; bodová mutace; Mutagenesis, Site-Directed; Phenylalanine; Glutamic Acid; rekombinantní proteiny; spektrofotometrie infračervená; vazba proteinů; Protein Structure, Secondary; mutageneze cílená; myši; aminokyseliny; Dose-Response Relationship, Drug; Recombinant Proteins; kyselina glutamová; Animals; vztah mezi dávkou a účinkem léčiva; Cysteine; genetické vektory; Genetic Complementation Test; Recombinant Fusion Proteins; cystein; Sodium-Potassium-Exchanging ATPase